Identifying factors of 'organizational information security management'. Issue 5 (19th August 2014) - Singh, Abhishek Narain; Gupta, M. P.; Ojha, Amitabh
Abstract : Purpose: Despite many technically sophisticated solutions, managing information security has remained a persistent challenge for organizations. Emerging IT/ICT media have posed new security challenges to business information and information assets. It is felt that technical solutions alone are not sufficient to address the information security challenge. It has been argued that organizations also need to consider the management aspects of information security. Consequently, literature, especially in the last decade, has witnessed various scholarly works in this direction. Therefore, a synthesis exercise is required to bring clarity on categorizing the issues of organizational Information Security Management (ISM) to take the research forward. This paper aims to identify management factors that address organizational information security challenges. Design/methodology/approach: Using a mix method approach, the paper adopts the qualitative (keyword analysis and experts' opinion) and quantitative (questionnaire survey) research routes. Exploratory factor analysis is conducted to find out the key factors of organizational ISM. Findings: The paper categorizes various organizational ISM functions into ten factors. Spanning across three levels (strategic, tactical and operational), these factors cover various management issues of organizational ISM. Originality/value: The paper takes the ISM literature forward by statistically validating the key management factors of organizational ISM. The study outcome should help to draw the attention of organizations towards the managerial challenges of organizational ISM.